Langmuir probe study of reactive magnetron discharge plasma in a three-component gas atmosphere; Instruments and Experimental Techniques; Vol. 59, iss. 6 - Evdokimov K. E. Kirill Evgenievich; Konishchev M. E. Maksim Evgenievich; Sun Zhilei; Pichugin V. F. Vladimir Fyodorovich (2016, 2016)
Title screen